MUHAMMAD MUSTAFA AZAMI: Kontribusi Pemikiran dan Bantahannya Terhadap Kajian Hadis Di Kalangan Orientalis - muhammad fajar adyatama (Holistic al-Hadis, 2020)
One of the controversial opinions of orientalists about hadith is that hadith is not as authentic as Muslims believe. According to orientalists, it is difficult to trust the hadith literature as a whole as an authentic record of all the sayings and actions of the Prophet Muhammad. This speculation caused reactions from Muslim scholars, including Muhammad Mustafa Azami. Azami found that the orientalists' doubts about the sanad system were caused by their methodological errors in studying the sanad system. This is because they generally do not examine the chain of transmission based on the main books of hadith, but on the books of fiqh and sirah which are compiled in a different way from the books of hadith. Azami refuted the conclusions of the orientalists by proving the authenticity of the hadith with various approaches. These include comparing the hadiths of many students' narrations with those of their teachers, comparing the statements of scholars from different times, comparing them with written documents, and comparing the hadiths with relevant verses of the Koran.